Integrated employee scheduling with known employee demand, including breaks, overtime, and employee preferences - Jhunievieve Soriano; Eugene Rex Jalao; Iris Ann Martinez (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: This research paper introduces an integrated employee scheduling problem that considers various real-life problems such as varying employee demand, different employee working conditions, and individual preferences regarding schedules. Design/methodology/approach: The proposed model, which is a combination of Analytic Hierarchy Process and Mixed Integer Linear Programming, is used to solve the problem with multi-dimensional objectives Findings: Results show that the proposed model generates optimal and feasible solutions for weekly employee schedules. Originality/value: Many employee scheduling problems in literature are able to solve the employee scheduling problem to a large extent but still do not fully reflect current realistic organizational problems such as varying employee demand per hour inteval, different employee working conditions on disjoint shifts and breaks, and individual preferences regarding schedules all at the same time.
Keywords: 650; scheduling; AHP; MILP; employee preferences